Non-discrimination in the World Trade Organization : the rules and exceptions - Davey, William J., 1949- ([The Hague] : Hague Academy of International Law, 2012)
International trade is conducted mainly under the rules of the World Trade Organization. Its non-discrimination rules are of fundamental importance. In essence, they require WTO members not to discriminate amongst products of other WTO members in trade matters (the mostfavoured- nation rule) and, subject to permitted market-access limitations, not to discriminate against products of other WTO members in favour of domestic products (the national treatment rule). The interpretation of these rules is quite difficult. Their reach is potentially so broad that it has been felt that they should be li.
The WTO/GATT system -- The concept and theory of non-discrimination rules -- Most-favoured nation treatment -- The exceptions to the most-favoured-nation obligation of Article I -- National treatment -- General exceptions -- Final observations.
"Full text of the lecture published in April 2012 in the Recueil des cours, Vol. 354 (2011)"--Page 2.
Includes bibliographical references (pages 337-353).
Print version record.
eBooks on EBSCOhost
Keywords: World Trade Organization; General Agreement on Tariffs and Trade (Organization); World Trade Organization; General Agreement on Tariffs and Trade (Organization); General Agreement on Tariffs and Trade (Organization); World Trade Organization; Foreign trade regulation; Tariff -- Law and legislation; Arbitration (International law); Commerce international -- Réglementation.; BUSINESS & ECONOMICS -- Exports & Imports; BUSINESS & ECONOMICS -- International -- General; BUSINESS & ECONOMICS -- International -- Marketing; POLITICAL SCIENCE -- International Relations -- Trade & Tariffs; Arbitration (International law); Foreign trade regulation; Tariff -- Law and legislation